Arginine-induced insulin secretion in endoplasmic reticulum - Umeda, Makoto; Hiramoto, Masaki; Watanabe, Atsushi; Tsunoda, Nobuyo; Imai, Takeshi (Biochemical and biophysical research communications, 2015)
Arginine, a semi-essential amino acid, is known as one of the most strongest insulin secretagogues in a glucose-dependent manner, but major mechanism is unknown. Arginine induced insulin secretion in mice as well as β cell line, NIT-1, in which more than 90% of intracellular insulin is prionsulin without arginine cultivation. Arginine administration reduced prionsulin amount in 30 s, then insulin is secreted from NIT1 cells. These data indicated that the target factor(s) for arginine-induced insulin secretion located in endoplasmic reticulum (ER). We established the screening system for identifying the arginine mimetics. Brazilian propolis, not Chinese propolis, induced insulin secretion. To identify target factor(s) of arginine induced insulin secretion, our previous study was that nanobeads technology facilitated us to purify chemical-target factors. This time we chose the other way, proinsulin associating factor purification and arginine-immobilized agarose. Three proinsulin associating factors and 5 arginine interacting factors were identified. Among theses factors, Calnexin (CNX) was the only one factor, which belonged to both groups, suggesting that CNX might play a key role in arginine-induced insulin secretion in ER. [Display omitted] •Proinsulin is main form without arginine.•Arginine convert proinsulin to insulin.•Brazilian propolis induced insulin secretion.•Arginine-interacted and proinsulin-associated factors were identified.